Roles of Clonal Integration in both Heterogeneous and Homogeneous Habitats - Zhang, Haijie; Liu, Fenghong; Wang, Renqing; Liu, Jian (Frontiers in Plant Science, 2016)
Many studies have shown that clonal integration can promote the performance of clonal plants in heterogeneous habitats, but the roles of clonal integration in both heterogeneous and homogeneous habitats were rarely studied simultaneously. Ramet pairs of Alternanthera philoxeroides (Mart.) Griseb were placed in two habitats either heterogeneous or homogeneous in soil nutrient availability, with stolon connections left intact or severed. Total biomass, total length of stolons, and number of new ramets of distal (relatively young) ramets located in low-nutrient environments were significantly greater when the distal ramets were connected to than when they were disconnected from proximal (relatively old) ramets located in high-nutrient environments. Total length of stolons of proximal ramets growing in low-nutrient environments was significantly higher when the proximal ramets were connected to than when they were disconnected from the distal ramets growing in high-nutrient environments, but stolon connection did not affect total biomass or number of new ramets of the proximal ramets. Stolon severing also did not affect the growth of the whole ramet pairs in heterogeneous environments. In homogeneous high-nutrient environments stolon severing promoted the growth of the proximal ramets and the ramet pairs, but in homogeneous low-nutrient environments it did not affect the growth of the proximal or distal ramets. Hence, for A. philoxeroides, clonal fragmentation appears to be more advantageous than clonal integration in resource-rich homogeneous habitats, and clonal integration becomes beneficial in heterogeneous habitats. Our study contributes to revealing roles of clonal integration in both heterogeneous and homogeneous habitats and expansion patterns of invasive clonal plants such as A. philoxeroides in multifarious habitats.